The Impact of Environmental Education Activities on Primary School Students' Environmental Awareness and Visual Expressions - Yesilyurt, Mustafa; Balakoglu, Mukadder Ozdemir; Erol, Mustafa (HIPATIA PRESS, 2020)
The aim of this research is to improve environmental awareness in primary school students. For this purpose, the study was carried out within the scope of action research pattern from qualitative research patterns. The study group was determined by selecting easily accessible samples. The study group consisted of second year students attending a state primary school in Gungoren District of Istanbul in the 2018-2019 academic year. The data of the study were obtained by the students' environmental pictures, observation forms and semi-structured interview forms. The data obtained were analyzed by content analysis. According to the findings of the research, it is determined that students who received environmental education, draw pictures enthusiastically and reflecting environmental awareness, also after interviews students gain awareness toward environment, empathized with nature and draw highly esthetically appreciated pictures.
Keywords: environmental awareness; primary school students; visual expression; empathy; CHILDREN; Education & Educational Research